Pengaruh Kepemilikan Saham Publik, Ukuran Kantor Akuntan Publik, dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Adelia J, Sherly; Agusti, Restu; Abdurrahman, Rezi (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
The purpose of this study is to examine and analyze the impact of public share ownership, the size of the public accounting firm, and company size on disclosures of corporate social responsibility (CSR). The population used in this research includes all banking companies listed on the Indonesia Stock Exchange in 2020–2022. At the same time, the sample was taken using the purposive sampling method, with a sample of 26 companies identified according to predetermined criteria. This study is quantitative in nature. Secondary data used in this study were taken from annual reports and sustainability reports. Then, multiple linear regression is the data analysis method using SPSS software version 26. Research results demonstrate that the size of the accounting firm and company size have an influence on CSR disclosure. Furthermore, public share ownership hasn't impacted CSR disclosure.Keywords: Public Share Ownership, Size Of Public Accounting Office, Company Size, CSR Disclosure